Interferon-γ Upregulates Expression of IFP35 Gene in HeLa Cells via Interferon Regulatory Factor-1 - Yang, Wei; Tan, Juan; Liu, Ruikang; Cui, Xiaoxu; Ma, Qinglin; Geng, Yunqi; Qiao, Wentao (PLOS ONE, 2012)
Background Interferon-induced 35-kDa protein (IFP35) plays important roles in antiviral defense and the progression of some skin cancer diseases. It can be induced by interferon-γ (IFN-γ) in multiple human cells. However, the mechanisms by which IFN-γ contributes to IFP35 induction remain to be elucidated. Methods/Principal Findings We identified the transcription start sites of IFP35 by 5′ rapid amplification of cDNA ends (RACE) and cloned the promoter of IFP35. Sequence analysis and luciferase assays revealed two GC boxes and an IFN-stimulated response element (ISRE) in the 5′ upstream region of the transcription start sites, which were important for the basal transcription of IFP35 gene. Furthermore, we found that interferon regulatory factor 1 (IRF-1) and IRF-2 could bind to IFP35 promoter and upregulate endogenous IFP35 protein level. Depletion of endogenous IRF-1 by interfering RNA reduced the constitutive and IFN-γ-dependent expression of IFP35, whereas depletion of IRF-2 had little effect on IFN-γ-inducible IFP35 expression. Moreover, IRF-1 was recruited to the ISRE site in IFP35 promoter in IFN-γ treated HeLa cells, as demonstrated by electrophoretic mobility shift and chromatin immunoprecipitation assays. Conclusions/Significance These findings provide the first evidence that IRF-1 and IRF-2 are involved in constitutive IFP35 expression in HeLa cells, while IRF-1 also activates IFP35 expression in an IFN-γ-inducible manner. Our data therefore identified a new IRF-1 and IRF-2 target gene, which may expand our current understanding of the versatile functions of IRF-1 and IRF-2.